Proliferation, Migration, and ECM Formation Potential of Human Annulus Fibrosus Cells Is Independent of Degeneration Status. (April 2020) - Hondke, Sylvia; Cabraja, Mario; Krüger, Jan Philipp; Stich, Stefan; Hartwig, Tony; Sittinger, Michael; Endres, Michaela
Objective: The objective was to evaluate the proliferating, migratory and extracellular matrix (ECM) forming potential of annulus fibrosus cells derived from early (edAFC) or advanced (adAFC) degenerative tissue and their usability as a possible cell source for regenerative approaches for AF closure. Design: EdAFC ( n = 5 Pfirrman score of 2-3) and adAFC (n = 5 Pfirrman score of 4-5) were isolated from tissue of patients undergoing spine stabilizing surgery. Cell migration on stimulation with human serum (HS), platelet-rich plasma (PRP), and transforming growth factor β-3 (TGFB3) was assessed by migration assay and proliferation was assessed on stimulation with HS. Induction of ECM synthesis was evaluated by gene expression analysis of AF-related genes in three-dimensional scaffold cultures that have been stimulated with 5% PRP or 10 ng/mL TGFB3 and histologically by collagen type I, type II, alcian blue, and safranin-O staining. Results: EdAFC and adAFC were significantly attracted by 10% HS and 5% PRP. Additionally, both cell groups proliferated under stimulation with HS. Stimulation with 10 ng/mL TGFB3 showed significant induction of gene expression of collagen type II and aggrecan, while 5% PRP decreased the expression of collagen type I. Both cell groups showed formation of AF-like ECM after stimulation with TGFB3, whereas stimulation with PRP did not. Conclusions: Our study demonstrated that AF cells retain their potential for proliferation, migration, and ECM formation independent of the degeneration status of the tissue. Proliferation, migration, and ECM synthesis of the endogenous AF cells can be supported by different supplements. Hence, endogenous AF cells might be a suitable cell source for a regenerative repair approaches.